2008
DOI: 10.1111/j.1365-2648.2008.04602.x
|View full text |Cite
|
Sign up to set email alerts
|

Music improves sleep quality in students

Abstract: Relaxing classical music is an effective intervention in reducing sleeping problems. Nurses could use this safe, cheap and easy to learn method to treat insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
142
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(153 citation statements)
references
References 32 publications
5
142
1
5
Order By: Relevance
“…Relaxation therapies have been proven to be effective against patient-specific insomnia symptoms in a number of studies 36) . In particular, music therapy has been reported to reduce anxiety and improve quality of sleep in several studies 37,38) . Relaxation techniques may be self-implemented at one's convenience and can result in improved sleep 39) .…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation therapies have been proven to be effective against patient-specific insomnia symptoms in a number of studies 36) . In particular, music therapy has been reported to reduce anxiety and improve quality of sleep in several studies 37,38) . Relaxation techniques may be self-implemented at one's convenience and can result in improved sleep 39) .…”
Section: Discussionmentioning
confidence: 99%
“…Using specific questionnaires for insomnia, such as insomnia severity or the PSQI, online treatment, psychoeducation, stimulus control instruction, sleep restriction, relaxation training and classical music were all found to lead to improvements in these two measures. 21,23 Subjects in the Tai chi group showed improvement in the PSQI. 22 A reduction in sleep latency, an increase in sleep efficiency (calculated using questionnaire responses) and a significant reduction in the frequency of hypnotic drug use in the CBT group were observed.…”
Section: Questionnairesmentioning
confidence: 99%
“…25 Half of the studies reviewed tested the effects of CBT on insomnia. [21][22][23]27,29,31 The other studies focused on therapies such as music, Yoga, Tai Chi Chi (a westernized and standardized version of Tai Chi, consisting of 20 simple and separate movements), relaxation and sleep hygiene.…”
Section: Questionnairesmentioning
confidence: 99%
“…The effectiveness of listening to loud music to improving the quality and quantity of sleep adolescents have not found. However, studies of Harmat et al 2008 revealed that 45 minutes of classical music at bedtime effectively reduced sleep problems in young adults [16] .…”
Section: Discussionmentioning
confidence: 99%